Ian Hamilton Finlay’s Little Sparta: Poetics of Artifact in Landscape Art - Kochetkova, Ekaterina S. (Actual Problems of Theory and History of Art, 2018)
This paper addresses the unique example of landscape art in the second half of the 20th century — the so-called Little Sparta, a park created by Scottish artist and poet Ian Hamilton Finlay (1925-2006). In this work, which was in the making for 50 years since 1966, there are certain elements rooted in the long-standing tradition of English landscape gardening; yet, this practice is reconsidered, and incorporates the experience of Conceptual art, as well as Postmodernist irony. Since Finlay was not only an artist but also a writer, the literary component plays a major part in his garden — in particular, the concrete poetry movement that maintained the indivisibility of the text’s message and its appearance. The present paper focuses on the concept of ‘garden poems’ or artifacts, which include objects, inscriptions, and natural surroundings. To create these artifacts, Finlay used the synthesis of various literary and artistic methods. The current paper investigates some of them, such as manipulations with the scale of objects and their material qualities, ways of visual and rhythmic organization of text, principle of vocabulary entry, playing with meanings and sounds of words, philosophical interpretations of everyday items, and searching for palpable forms to illustrate abstract notions. The classical theme of genius loci is of special importance here, as it is rendered unconventionally through ‘signing’ the landscape and positioning ‘focus frames’ within it, to guide the viewer’s eye.
Keywords: Little Sparta; Ian Hamilton Finlay; landscape art; garden art; concrete poetry; Postmodernist art; classical tradition; genius loci; British art; Scottish art